Comparing the use of silicone and polyurethane Peripherally Inserted Central Catheters in newborns: A retrospective study. Issue 23 (20th September 2021) - Gomes de Souza, Nayana Maria; Silveira Rocha, Rebeca; Pinheiro Ferreira, Roberta; Bastos da Silveira Reis, Claudia; Souza Bandeira, Roberta Sthephanie; Façanha Melo, Ana Paula
Abstract: Aims and objectives: To compare polyurethane and silicone peripherally inserted central catheters (PICCs) in newborns regarding the success rates of insertion and duration and the reasons for nonelective removal. Background: Previous studies have attempted to identify predictors of PICC complications in newborns, such as lower extremity insertion or femoral catheter insertion, procedures that require 60 minutes or more, duration longer than 30 days and non‐central position of the catheter tip. However, there is little evidence on which type of PICC material causes less complications, especially in newborns. Design: Retrospective cohort, guided by the STROBE tool. Methods: We divided the newborns into two groups according to the type of PICC material: polyurethane and silicone. Our sample was composed of 449 PICCs, of which 246 polyurethane PICCs and 203 silicone PICCs, inserted in 294 newborns. Bivariate analysis was performed for data comparison. All statistically significant variables in the bivariate analysis were included in the logistic regression ( p  ≤ .05). Results: Of the 449 PICCs that we analysed, the central position of the catheter tip predominated for both types of materials, with a higher prevalence of false passage for the polyurethane group. There was no difference between the average duration. The incidence of nonelective PICC removal was 49.27% for the silicone group, and infiltration/extravasation and rupture were among the reasons for nonelective removal. Conclusion: The overall success rates in the insertion and duration of the PICC were almost identical for both types of material, despite the high incidence of false passage for polyurethane PICCs. Nonelective removals were higher for silicone PICCs, which also had a higher incidence for infiltration/extravasation and rupture. Relevance to clinical practice: Can contribute to the knowledge of the strengths and weaknesses of polyurethane and silicone PICCs, with a view to reduce the incidence of nonelective removals.